Semantic Analysis of Slang Expressions Among Medanese Generation Z on Instagram - Nauli Hosianna Napitu; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study aims to explore the semantic characteristics of slang words used by Generation Z in Medan during communication on Instagram. The objectives are to identify and classify the types of slang vocabulary, analyze their semantic meanings, and examine the forms of slang commonly used by Medanese youth. This research uses a qualitative descriptive method with a digital etgraphy approach, focusing on observations of Instagram accounts belonging to teenagers and young adults from Medan. The findings reveal that the slang used falls into several categories: acronyms, clipped words, blended words, local dialect slang, and figurative or metaphorical slang. Many of these expressions are influenced by local culture, national trends, and global digital communication. The meanings of slang words are not only literal but also contextual and symbolic, shaped by the social interactions and cultural background of the users. The study concludes that slang serves as a tool for self-expression, group identity, and creative linguistic innovation among Medanese Generation Z. It reflects how youth navigate their cultural identity while engaging in informal communication through social media. This research contributes to the understanding of how language evolves in digital spaces and how regional identity influences online discourse.